Topical issues of etiology, consequences, and treatment of secondary lactase deficiency in children: literature review and results of our research - Yu.V. Marushko; O.A. Dmytryshyn; O.A. Bovkun; T.V. Iovitsa; В.Ya. Dmytryshyn (Zaslavsky O.Yu., 2024)
The article presents the review and synthesis of modern data of scientific publications from the Scopus, Web of Science databases, and the register of professional scientific publications of Ukraine on the causes, consequences, and methods of correcting secondary lactase deficiency in children. The features of secondary lactase deficiency in antibiotic therapy and other pathological changes in the gastrointestinal tract that develop with the use of antibacterial drugs are described. The authors present their own data on the treatment of secondary lactase deficiency caused by antibiotic therapy in school-age children. It has been found that the use of the lactase enzyme in children with secondary lactase deficiency, which has developed on the background of antibiotic therapy, leads to positive dynamics of clinical manifestations already on the third day of taking the drug, and it is a more effective method of correcting these symptoms compared to only dietary recommendations and limited consumption of lactose products. The criteria proposed for prescribing a hydrogen breath test to diagnose secondary lactase deficiency developed on the background of antibiotics are as follows: the presence of clinical manifestations (diarrhea, abdominal pain, excessive gas, bloating, nausea, vomiting) that occurred during antibiotic therapy and are aggravated by the use of lactose-containing products; repeated courses of antibacterial drugs (every 3-4 months) according to the anamnesis; changes in the results of the coprogram (yellow, mushy, foamy feces with an acidic odor, the presence of mucus, fecal pH less than 5.5, a small amount of iodophilic flora); no signs of inflammatory bowel disease according to the results of the coprogram (blood, leukocytes); negative results of rapid tests for the detection of Clostridium difficile toxins A and B in the feces. The use of these criteria to diagnose secondary lactase deficiency associated with antibiotics will improve the frequency of its detection and the reasonable prescription of lactase drugs to reduce the severity of clinical manifestations of lactase deficiency and restore the functional state of the gastrointestinal tract more quickly.